EXERGOECONOMIC ANALYSIS OF IHOVBOR GAS POWER PLANT (Nigerian Journal of Technology, 2018)
Exergoeconomic parameters of Ihovbor Gas Power plant were determined in this study. To achieve this, the exergy of each stream, the economic cost of the plant components, the exergetic costs of each stream and the exergoeconomic evaluation of each component were determined. The average exergy efficiency of GTs ONE, TWO, THREE and FOUR were found to be 59.32%, 60.83%, 59.80% and 60.38% respectively and it decreased with increase in ambient temperature. The exergy destruction cost was greatest in the combustor (average of 1596.175$/hr), the relative cost difference was greatest in the air compressor with an average ratio of 0.36585, the exergoeconmic factor of the gas turbine was greatest (91.84%) and the average cost of power generation was found to be $0.0162/kWhr. Exergoeconomic parameters can be used as tools for energy audit and determining the running costs of power plants and power generation. http://dx.doi.org/10.4314/njt.v37i4.10